2006
DOI: 10.1111/j.1399-3054.2006.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved development of microspore‐derived embryo cultures of Brassica napus cv Topaz following changes in glutathione metabolism

Abstract: Glutathione has been shown to play an important role during embryo development in both plant and animal systems. The effects of altered glutathione metabolism during microspore-derived embryos (MDEs) of Brassica napus were investigated following exogenous application of reduced glutathione (GSH), its oxidized form (GSSG) and buthionine sulfoximine (BSO), an inhibitor of glutathione de novo synthesis. Applications of BSO which lowered the cellular glutathione redox status, i.e. GSH/(GSH þ GSSG), enhanced signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 40 publications
7
71
0
Order By: Relevance
“…If applied in the medium after 7 days of culture, BSO induces an oxidized glutathione environment by inhibiting GSH synthesis (GriYth and Meister 1979), thereby lowering the cellular GSH/ GSH + GSSG ratio. This metabolic switch improves embryo quality, as measured by the enhanced conversion frequency, and induces major structural changes in the developing embryos (Belmonte et al 2006). Histological analyses revealed that compared to their control counterparts, BSO-treated embryos form well organized meristems and accumulate storage products in a similar pattern to that observed in seed embryos.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…If applied in the medium after 7 days of culture, BSO induces an oxidized glutathione environment by inhibiting GSH synthesis (GriYth and Meister 1979), thereby lowering the cellular GSH/ GSH + GSSG ratio. This metabolic switch improves embryo quality, as measured by the enhanced conversion frequency, and induces major structural changes in the developing embryos (Belmonte et al 2006). Histological analyses revealed that compared to their control counterparts, BSO-treated embryos form well organized meristems and accumulate storage products in a similar pattern to that observed in seed embryos.…”
Section: Introductionmentioning
confidence: 83%
“…Induction of embryo development from B. napus cv Topas DH4079 microspores and applications of BSO were carried out exactly as reported by Belmonte et al (2006). For this experiment days in culture were counted after the imposition of the heat shock treatment.…”
Section: Brassica Napus Embryo Development and Bso Treatmentsmentioning
confidence: 99%
See 3 more Smart Citations